NOVEL GASTRO-RETENTIVE POLYMERIC MICROSPHERES: AN APPROACH FOR INCREASED BIOAVAILABILITY AND AN ONCE DAILY DOSING OF TERBUTALINE SULPHATE - El-menshawe, Shahira F.; Abdeltwab, Amany M.; Mohamed, Ahmed I. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The purpose of this study was to develop multi-unit alginate-copolymer adhesive microspheres to achieve a sustained release of terbutaline sulphate (TBS) and overcome the hepatic first pass effect so as to enhance its bioavailability. Methods: The microspheres were prepared using inotropic gelation method and different concentration of sodium alginate alone or in combination with other polymers as well as using chitosan as a coating polymer in some formulations. All of the prepared microspheres were evaluated for yield, size, encapsulation efficiency, in vitro release and mucoadhesivity. The selected formulations (F11 and F19) were further subjected to differential scanning calorimetry, Fourier transform infrared spectroscopy, stability and in vivo bioavailability studies. Results: The prepared microspheres exhibited quite widely varying encapsulation efficiencies from 20 to 74. 8 % and its mean diameter was in range of 963. 3-1. 635 Âµm. The in vitro release study showed a sustained release profile. The selected formulations were further subjected to differential scanning calorimetry and FTIR which confirm the absence of any incompatibility. X-ray diffraction suggests the amorphous nature of the drug after encapsulation. The selected formulation F11 and F19 showing encapsulation efficiency higher than 55 %, an amount of drug released within 50-60 % after 8 h and a relative bioavailability of 283. 84 % and 202. 04 % respectively compared with the marketed oral AironylÂ® tablets. Conclusion: The prepared microspheres were significantly efficient to achieve a sustained release of terbutaline sulphate with a higher relative bioavailability in comparison with the oral marketed tablet.